An Investigation of the Role of Phase Angle in Malnutrition Risk Evaluation and Clinical Outcomes in Patients with Head and Neck or Brain Tumors Undergoing Radiotherapy - Emir, Kubra Nur; Demirel, Birsen; Atasoy, Beste M. (Routledge Journals, Taylor & Francis Ltd, 2024)
This cross-sectional study aimed to investigate the role of bioelectrical impedance analysis (BIA) and phase angle measurement in assessing malnutrition in head and neck (n = 37) and brain (n = 63) tumor patients received radiotherapy. Common nutritional screening and assessment tests were used to identify malnutrition in the patients. Each patient underwent these tests once, along with phase angle measurement. Additionally, inflammation parameters, including neutrophil lymphocyte ratio (NLR), platelet lymphocyte ratio (PLR), and systemic inflammatory index (SII), were calculated. All study results were correlated with the phase angle cutoff point of 5.72(degrees). The phase angle demonstrated significant correlations with subjective global assessment (SGA), mini nutritional assessment (MNA) scores, BIA parameters, nutritional index, NLR, and SII (p < 0.05). Moreover, in head and neck tumor patients, those with higher standardized phase angle values exhibited significantly better two-year overall survival (32.1% vs. 87.5%, p = 0.006). The phase angle measurement is a convenient, noninvasive, and reproducible method that can complement existing tools for assessing malnutrition risk in radiotherapy patients. The significant correlations observed between the phase angle and various nutritional, inflammation markers and prognosis highlight its potential utility. Further studies incorporating a larger patient cohort will be beneficial in establishing a standard phase angle reference value for cancer patients.
Keywords: Bioelectrical-Impedance Analysis; Subjective Global Assessment; Quality-Of-Life; To-Lymphocyte Ratio; Nutritional-Status; Body-Composition; Cancer Patients; Mass; Prognosis